Distinct mitogenic and cell fate specification functions of wingless in different regions of the wing. - Neumann, C.J.; Cohen, S.M. (Development, 1996)
Patterning and proliferation are coordinately controlled in the development of Drosophila imaginal discs. Localized expression of decapentaplegic (dpp) at the anterior-posterior and wingless (wg) at the dorsal-ventral compartment boundaries controls growth of the wing with respect to the A/P and D/V axes. The growth-promoting effects of these organizers are thought to be indirect, since growth is dispersed throughout the disc, and is not localized near the sources of wg or dpp. wg has also been implicated in proximal-distal patterning of the wing hinge. In this report, we present evidence that wg is principally required for local cell proliferation in the hinge. Loss of wg expression leads to a local reduction in cell division, resulting in the deletion of a distinct set of wing hinge structures. Ectopic activation of the wg pathway in cells of the wing hinge leads to overproliferation without repatterning, indicating that wg acts as a mitogen in this part of the disc. By contrast, overexpression of wg in the wing blade leads to repatterning and only secondarily to proliferation. These results suggest that the Wg signal elicits very different responses in different regions of the wing imaginal disc.